2023
DOI: 10.1186/s12888-023-04681-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the relationship between bullying and depressive symptoms in children and adolescents

Abstract: Childhood and adolescence are critical periods for physical and mental development; thus, they are high-risk periods for the occurrence of mental disorders. The purpose of this study was to systematically evaluate the association between bullying and depressive symptoms in children and adolescents. We searched the PubMed, MEDLINE and other databases to identify studies related to bullying behavior and depressive symptoms in children and adolescents. A total of 31 studies were included, with a total sample size… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Consistent with our findings, a cross-sectional study of 2,155 students found that participants who were bullied had higher levels of depression [ 28 ]. Another meta-analysis suggested that children and adolescents who experience bullying were associated with a higher incidence of depression, with an odd ratio of 2.77 [ 62 ]. A study used an SEM to explore the relationship between bullying and depressive symptoms in 4,289 Italian adolescents and found a significant positive association [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, a cross-sectional study of 2,155 students found that participants who were bullied had higher levels of depression [ 28 ]. Another meta-analysis suggested that children and adolescents who experience bullying were associated with a higher incidence of depression, with an odd ratio of 2.77 [ 62 ]. A study used an SEM to explore the relationship between bullying and depressive symptoms in 4,289 Italian adolescents and found a significant positive association [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 A recent meta-analysis comprising >133,000 adolescents showed that bullying was associated with nearly 3 times the risk of depression compared to those not bullied. 42 Further, overweight/obese individuals experienced significantly higher risk to be bullied. 43 This provides for a 'negative feedback loop' wherein which bullying may lead to subsequent depression and consequent weight-gain which then results in these individuals be further bullied.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Youth can be involved in bullying incidents as the bully, victim, or bullyvictim (those who report both perpetration and victimization). Bullies are at increased risk of becoming involved in delinquency, conduct problems, and crime [9,10] and are more likely to exhibit social problems, aggression, and externalizing behaviors [11,12]. Youth who are victims of bullying have been shown to exhibit a number of important social deficits, including low levels of social acceptance, poor friend and peer support, inadequate social skills and social assertiveness, and greater loneliness [13][14][15].…”
Section: Introductionmentioning
confidence: 99%